2010
DOI: 10.1097/phh.0b013e3181bedb49
|View full text |Cite
|
Sign up to set email alerts
|

Defining Quality Improvement in Public Health

Abstract: Many industries commonly use quality improvement (QI) techniques to improve service delivery and process performance. Yet, there has been scarce application of these proven methods to public health settings and the public health field has not developed a set of shared principles or a common definition for quality improvement. This article discusses a definition of quality improvement in public health and describes a continuum of quality improvement applications for public health departments. Quality improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 1 publication
0
71
0
2
Order By: Relevance
“…23 It is much longer than the one used in the 2008 Profile study and may not be practical in the context of a lengthy survey covering many topics. Nonetheless, the definition used in the 2008 Profile survey does include several key concepts from the consensus definition, including "deliberate, defined process," "achieve measurable improvements," and "impacting the health of the community."…”
Section: • Resultsmentioning
confidence: 99%
“…23 It is much longer than the one used in the 2008 Profile study and may not be practical in the context of a lengthy survey covering many topics. Nonetheless, the definition used in the 2008 Profile survey does include several key concepts from the consensus definition, including "deliberate, defined process," "achieve measurable improvements," and "impacting the health of the community."…”
Section: • Resultsmentioning
confidence: 99%
“…In health and welfare, QI has become an important aspect for service safety and effectiveness reasons while delivering better quality care (Riley et al, 2010). Quality improvement, or at least the idea, has become a competition issue.…”
Section: Quality Improvement Knowledgementioning
confidence: 99%
“…[2] On the contrary, other studies have shown that there is a difficulty in engaging health care professionals in organizational improvements of care processes. [8][9][10][11] The literature also describes health care organizations' culture as characterized by limited trust and limited collaboration between different occupational groups and organizational levels. [12,13] Despite these hindering factors, there is potential to overcome these obstacles.…”
Section: Introductionmentioning
confidence: 99%